2005
DOI: 10.1089/jop.2005.21.121
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Hypotensive DP-Class Prostaglandin Receptor Affinities Determined by Quantitative Autoradiography on Human Eye Sections

Abstract: The aim of this study was to define the localization and pharmacology of DP-prostaglandin receptors in human eye sections using a novel DP-antagonist radioligand ([3H]-BWA868C), using various intraocular pressure (IOP)-lowering DP-prostaglandins and the technique of quantitative autoradiography on 20-microm sections of frozen human eyes. [3H]BWA868C yielded well-defined autoradiograms of DP-receptors in human eyes with up to 82% specific binding. High densities of DP-receptors were associated with the ciliary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Furthermore, studies of the vasoactive effect of prostaglandins are hampered by the possible existence of still unidentified prostaglandins, by the fact that specific antagonists to receptors of some already-known prostaglandins are missing, and by the fact that known agonists and antagonists may show cross-reactivity to several receptors. 7 These facts may provide the background for the finding that, after preconstriction, all the studied prostaglandins showed a vasorelaxing effect at the highest concentrations used, that PGF 2␣ showed the opposite effect by decreasing the vascular tone after the vessels had been precontracted with U46619, and that CTA2 and U46619 had different effects, although both have been characterized as specific agonists to the TP receptor. 14 It has also been shown that the involvement of prostaglandins in the tone regulation of retinal arterioles displays considerable species variation, 4,15 but despite this, no functional pharmacologic differences have hitherto been shown in the tone regulation in porcine and human retinal arterioles.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Furthermore, studies of the vasoactive effect of prostaglandins are hampered by the possible existence of still unidentified prostaglandins, by the fact that specific antagonists to receptors of some already-known prostaglandins are missing, and by the fact that known agonists and antagonists may show cross-reactivity to several receptors. 7 These facts may provide the background for the finding that, after preconstriction, all the studied prostaglandins showed a vasorelaxing effect at the highest concentrations used, that PGF 2␣ showed the opposite effect by decreasing the vascular tone after the vessels had been precontracted with U46619, and that CTA2 and U46619 had different effects, although both have been characterized as specific agonists to the TP receptor. 14 It has also been shown that the involvement of prostaglandins in the tone regulation of retinal arterioles displays considerable species variation, 4,15 but despite this, no functional pharmacologic differences have hitherto been shown in the tone regulation in porcine and human retinal arterioles.…”
Section: Discussionmentioning
confidence: 81%
“…Furthermore, the effect of the PGE rec antagonist on ATP-induced vasodilation was not found in adenosine-induced vasodilation, which does not depend on the perivascular retina. 2 It has been shown that PGE receptors exist in ocular tissue, 6,7 and that PGE may induce vasodilation after intravitreal injection in minipigs, 5 an effect that can be reversed by indomethacin. 17 Furthermore, intravenously administered PGE 1 and PGE 2 increase retinal perfusion in rats 18 although this effect cannot be reproduced with PGE 1 in humans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prostaglandin receptor FP could also be identified [60,87,90,94,[98][99][100][101]; however, it is located mainly in the inner portion of the ciliary muscle [91,92,97]. Beside these two groups, the TP receptor [90] and the DP receptor [93,95,102,103] were described for the human ciliary muscle; IP receptors were not mentioned.…”
Section: Membrane Elements and Receptorsmentioning
confidence: 99%